Firm Size Moderating-Investor Perception Mediation: Green Accounting, Carbon-Audit Factors on Financial Performance - Mohamad Zulman Hakim; Muhammad Khoirul Insan; Hesty Erviani Zulaecha; Dewi Rachmania; Adelia Destianti (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the effects of green accounting, carbon tax, carbon emission disclosure, audit opinion, and audit quality on financial performance. It also investigates the mediating role of investor perception and the moderating role of firm size in explaining these relationships. Design/methodology/approach: This study uses panel data from energy sector companies listed on the Indonesia Stock Exchange during 2021–2024. The sample was selected using purposive sampling. Data were analyzed using panel regression models, including the Common Effect Model, Fixed Effect Model, and Random Effect Model, with model selection based on the Chow, Hausman, and Lagrange Multiplier tests. The analysis was conducted using EViews 12. Findings/Results: The results show that green accounting, carbon tax, carbon emission disclosure, audit opinion, and audit quality have positive and significant effects on financial performance. Firm size strengthens the effects of green accounting and carbon tax on financial performance, but does not significantly moderate the effects of carbon emission disclosure, audit opinion, or audit quality. Investor perception partially mediates the relationships between the independent variables and financial performance, except in the case of audit quality. Originality/Value: This study highlights the importance of integrating environmental accounting, carbon-related factors, and audit-related variables in explaining financial performance. The findings imply that investor perception and firm size are important mechanisms in strengthening the relationship between sustainability-related practices and firm performance.